Complaints: Mechanisms for prisoner participation? - Banwell-Moore, Rebecca (European journal of criminology, 2023)
In prisons, participatory mechanisms can foster important outcomes including fairness, legitimacy and dignity. Complaints are one significant (symbolic) mechanism facilitating prisoner participation. Ombud institutions/Ombudsmen handle complaints externally, providing unelected accountability mechanisms and overseeing prisons around the world. A fair complaints process can stimulate prisoner voice, agency and rights protection, potentially averting self-harm and violence, and facilitating systemic improvements. However, complaints mechanisms are little studied. Addressing this gap, we: i) contextualise discussion by demonstrating that prisoners? actions have directly shaped complaints mechanisms available today; ii) outline prison complaints mechanisms in the case study jurisdiction of England and Wales; and iii) provide a critical review of literature to assess whether prison complaints systems are, in practice, participatory, inclusive and fair? We conclude that complaints mechanisms hold clear potential to enhance prison legitimacy, facilitate prisoner engagement and agency, and improve wellbeing and safety. However, myriad barriers prevent prisoners from participating in complaints processes, including culture, fear, accessibility, timeliness, emotional repression, and bureaucracy. The process of complaining and experiences of these barriers are uneven across different groups of prisoners. Our article provides a springboard for future empirical research.